2005
DOI: 10.1002/cbic.200400459
|View full text |Cite
|
Sign up to set email alerts
|

Production of the Tubulin Destabilizer Disorazol in Sorangium cellulosum: Biosynthetic Machinery and Regulatory Genes

Abstract: Myxobacteria show a high potential for the production of natural compounds that exhibit a wide variety of antibiotic, antifungal, and cytotoxic activities. The genus Sorangium is of special biotechnological interest because it produces almost half of the secondary metabolites isolated from these microorganisms. We describe a transposon-mutagenesis approach to identifying the disorazol biosynthetic gene cluster in Sorangium cellulosum So ce12, a producer of multiple natural products. In addition to the highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 68 publications
0
80
0
4
Order By: Relevance
“…Instead, discrete AT genes were detected upstream of the megasynthase open reading frames (Table 2). This architecture, which has been recently described as trans-AT PKS (34), is also known from a smaller number of other systems, such as the pederin and onnamide PKSs from bacterial endosymbionts of beetles (34) and sponges (36), respectively; the leinamycin (lnm) PKS from Streptomyces atroolivaceus (7); the mupirocin PKS from Pseudomonas fluorescens (11); the myxovirescin (TA) PKS from Myxococcus xanthus (30); and others (4,19,40). Experimental evidence presented for the LnmG AT suggested that the discrete ATs act iteratively by loading malonyl coenzyme A (CoA) onto all PKS modules during polyketide synthesis (7).…”
Section: Mass Spectrometric (Ms) Analysis (I) Maldi-tof Msmentioning
confidence: 99%
“…Instead, discrete AT genes were detected upstream of the megasynthase open reading frames (Table 2). This architecture, which has been recently described as trans-AT PKS (34), is also known from a smaller number of other systems, such as the pederin and onnamide PKSs from bacterial endosymbionts of beetles (34) and sponges (36), respectively; the leinamycin (lnm) PKS from Streptomyces atroolivaceus (7); the mupirocin PKS from Pseudomonas fluorescens (11); the myxovirescin (TA) PKS from Myxococcus xanthus (30); and others (4,19,40). Experimental evidence presented for the LnmG AT suggested that the discrete ATs act iteratively by loading malonyl coenzyme A (CoA) onto all PKS modules during polyketide synthesis (7).…”
Section: Mass Spectrometric (Ms) Analysis (I) Maldi-tof Msmentioning
confidence: 99%
“…BecA and BecC are thought to complete the synthesis of the acyl chain, which is subsequently modified into an aminoacyl. Such splitting of modules on separate proteins has been reported in several cases (7,23,32,36). The structure of ML-449 indicates incorporation of one additional acetate unit compared to what is observed in BE-14106 biosynthesis.…”
Section: Resultsmentioning
confidence: 66%
“…These trans-AT PKSs include those responsible for production of the disorazoles [76,77], kirromycin [78 -80] and several others [75,81,82]. A potential engineering strategy involves the selective inactivation of a cis-AT domain and complementation using a trans-AT with differing specificity [9].…”
Section: Trans-acyltransferase Complementationmentioning
confidence: 99%
“…ACP transacylase [77] erythromycin AT6null/ bryostatin AT1 [78] erythromycin AT6null/ bryostatin AT2 [78] MMCoA/MCoA Figure 3. Previous attempts to engineer AT domain substrate specificity.…”
Section: Introductionmentioning
confidence: 99%